Learning the Discovery Learning Model How to Blended Learning in Practicum Using a Simple Volumetric Gasometer to Support Scientific Literacy - Annisa Rahmawati; Widi Purwianingsih; Bambang Supriatno (Jurnal Penelitian Pendidikan IPA, 2023)
Education in the 21st century requires innovation and creativity as well as skills including scientific literacy skills and numeracy literacy, one of which is experimental learning. Often experiments are constrained by insufficient learning time so that learning becomes less meaningful. The purpose of this study was to determine the effect of applying the discovery model using the blended learning method using a simple volumetric gasometer in supporting scientific literacy. This research is an experimental research conducted in February 2023 at a Bandung high school. The research population was 432 students of class X at a senior high school in Bandung, which were divided into 12 classes. The sampling technique used simple random sampling so that 70 students were obtained consisting of 35 people from one control class and 35 people from one experimental class. The instrument used is a PISA question with the theme of innovation in alcoholic fermentation technology. Instruments were in the form of multiple choice questions and true wrong choice questions to measure scientific literacy profiles. Based on the results of the research, it was found that the learning outcomes of the discovery model by means of blended learning with practical methods using a simple volumetric gasometer can support scientific literacy.